Mechanisms of microbubble mediated drug delivery - Aron, M; Pereno, V; Carugo, D; Vince, O; Kuimova, M; de la Serna, J; Sezgin, E; Eggeling, C; Stride, E (Springer, 2017)
There is now a substantial literature demonstrating the potential of surfactant stabilised microbubbles as drug delivery agents; particularly in combination with therapeutic ultrasound. Microbubbles provide a means of encapsulating drugs to avoid interaction with healthy tissue.